Strengthening the role of the family in supporting the social interaction and well-being of children with autism spectrum disorder - Athbah, Saad Yahya (Edelweiss Applied Science and Technology, 2024)
The purpose of this study was to explore the issue of strengthening the family in supporting the social interaction and well-being of children with autism in Jeddah, Saudi Arabia. The study used a descriptive approach and relied on the social survey. The sample of the study included 110 parents of children with ASD, who were selected randomly. The questionnaire of 35 items was used as an instrument for the study to collect data. The results showed parents regard discovering the problem of ASD among their children to be a very important and effective aspect. On the other hand, they think the institutions and care centres have a low role in supporting them when dealing with their children. The findings did not reveal significant differences between the parents according to their gender and level of education. The results showed that the parents from both genders believe that there are challenges facing them to help their children become socially interactive and the role of institutions and care centres is not effective. The findings did not reveal significant differences between the parents according to their gender and level of education. The results showed that the parents from both genders believe that there are challenges facing them to help their children become socially interactive and the role of institutions and care centres is not effective.